TASTE ALTERATION AND QUALITY OF LIFE OF PATIENTS RECEIVING CHEMOTHERAPY - Antony, Anooja; Pavithran, Sheela (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The study was conducted with the aim to determine the taste alteration (TA) and its relation with quality of life (QOL) of patients receiving chemotherapy. Methods: The present study was undertaken among 100 patients receiving cancer chemotherapy with the aim of identifying the commonly experienced TA and its relation with QOL of the patients. The patients were selected by convenience sampling from a selected Cancer Institute in Kerala. Results: The study reported that TA was present in all the patients receiving chemotherapy ranging from mild to severe where 50% had moderate and 9% had severe alteration in taste. There were 19% patients who had poor and 45% who had average QOL. The TAs had a moderately negative correlation with QOL (r=−0.51) indicating that an increase in TA decreases the QOL. Conclusion: The study evinces that TA is a common side effect of chemotherapy which often impacts the QOL negatively. Hence, it is essential to understand the types of TA and the specific drug causing it. This will enable the health-care team members to develop treatments for these conditions and educate patients regarding the strategies to be adopted to manage the problem, thereby improving patients' QOL.